The bone ultrastructural changes on combat trauma condition represented by scanning electron microscopy - Borzykh, N. O.; Strafun, S. S.; Savosko, S. I.; Makarenko, O. M.; Laksha, A. A. (Морфологія / Morphologia / Morfologìâ, 2018)
ABSTRACT. Background. The row of factors influences on a result to the regeneration, in particular weight of destruction of bone, state of regional circulation of blood, inflammation. For today one of the the least studied and difficult types of breaks there are gunshot traumas of extremities. Objective.The general analysis of fragments, splits character and microelement composition was carried out. Furthermore, the experimental samples were compared with the bone fragments of injury caused by household trauma. Methods. Using the scanning electron microscopy (SEM) we have investigated the bone fragments of injury caused by combat trauma (gunshot and mine-blast wound). Results. According to SEM the bone fragments contained the mineralized matrix with lacunae and tubules. A cortical zone of the bone fragments consisted of lamellar bone; the Haversian canal and osteoid plates were found on the bone splits. The character of the bone split was clearly defined by osteons’ lamellas location. Into intact bone the osteons’ lamellas form the continuous concentric layers around Haversian canal. Consequently, the bone split after combat trauma took place in the osteons’ lamellas. The presence of such defects in the bone fragments should be considered as a factor of further bone reorganization, osteoporosis-like bone matrix transformation and instability during the osteosynthesis. Conclusion. The results of chemical analysis showed the statistically significant decrease of fluorine content (F) (р<0,01) and the decreasing tendency of calcium (Ca), sodium (Na), phosphorus (P) in the bone fragments after combat trauma. The Ca/P ratio did not change significantly while Na/Mg, Ca/S and Ca/C ratio tended to decrease. In two bone samples the increased levels of sulfur (S) and carbon (C) to the total chemical elements composition were determined. We make an assumption that emergence of the last elements into the bone fragments may be connected with the total content of hydroxyapatite decrease and presence of combustion products residues or other sulfur-containing flammable substances. In this way, taking into account the SEM and spectrometry (energy-dispersive spectrometer) results we make a conclusion that the microcracks density into bone matrix after combat trauma is higher than after household trauma. The cause of such effect is the killer kinetic action on the bone.